Khoekhoe lexical borrowing in Namaqualand Afrikaans - Christie, Camilla Rose (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2020)
Although several languages in the Khoekhoe branch were historically spoken alongside Afrikaans in bilingual speech communities throughout the Western and Northern Cape, the last century has seen abrupt and catastrophic language loss, resulting in a shift from a bilingual to a monolingual paradigm. However, a number of ethnobotanical surveys conducted in the Namaqualand region of the Northern Cape over the last forty years have recorded the retention of Khoekhoe-branch plant names by monolingual Afrikaans speakers. Such surveys make no attempt to source these loanwords to their Khoekhoe-branch targets, do not make use of the standardised Namibian Khoekhoe orthography, and often resort to transcribing loaned click consonants using only 't'. This study undertakes a sociohistorical linguistic investigation into the etymological origins and contemporary usage of these loaned plant names in order to develop a clearer understanding of language contact and lexical borrowing in the Namaqualand region. Following the lexicographical compilation of a representative corpus of loanwords, this study conducts a series of semi-structured interviews with monolingual speakers of Namaqualand Afrikaans. Qualitative sociolinguistic analysis of these interviews reveals that, although loanwords are perceived to be of Nama origin, they are semantically opaque beyond pragmatic reference. Preliminary phonological observations identify a loss of phonemic contrastivity in loaned clicks coupled with a high incidence of variability, and suggest epenthetic stop insertion and epenthetic nasalisation as two possible strategies facilitating click loan. Synthesising these ob servations, this study speculates that the use of loanwords hosting clicks may enjoy a degree of covert prestige in Namaqualand Afrikaans, which may in turn shed light on historical sociolinguistic processes of click diffusion. It recommends that urgent and immediate attention be focused on the usage, sociolinguistic status, and regional variation of Nama within the Northern Cape, and advocates strongly for cooperation and improved communication between linguists and ethnobotanists.
Keywords: Code switching (Linguistics); Afrikaans language -- Foreign elements -- Nama; Nama language -- Foreign elements -- Afrikaans; Afrikaans language -- Phonology; Nama language -- Phonology